Sosialisasi Sistem Scheduling Appointment Berbasis Website pada Poli Rawat Jalan di RSUD Sidoarjo Barat - Ibrahim, Mochammad Malik; Rakhmawati, Fitria; Monika, Rizki; Harsanti, Eka Yuliani Putri; Lestari, Erika Puji; Laylia, Evania Risky; Melani, Ria Irmanda Putri; Puspita, Wulan Ayu; Putri, Anggilia Difani (STIKES Yayasan RS.Dr.Soetomo, 2025)
Digitalization in the health sector has been regulated in the Minister of Health's Decree Number HK.01.07/Menkes/1559/2022. This transformation effort can help provide optimal services. One form of this digitalization adoption can be seen in the presence of digital appointments, which can also be referred to as online service reservations. Service reservations or making appointments with doctors, which were previously done conventionally, can now be done online to make it easier for both patients and staff. RSUD Sidoarjo Barat has a digital appointment system based on a website that can be utilized by both old and new patients. However, many patients are still unaware of the existence of this website. Based on secondary data from patient visits on January 4 and 6, 2025, there were 196 patients who registered online out of a total of 746 patients, with a percentage of 26%. The small number of patients who chose to register online is because many patients are not yet aware of the availability of online registration. The purpose of this community service is to educate patients about the benefits of creating schedules online and how to schedule online. The method used was outreach by approaching outpatient clinic patients who were waiting at the registration desk of RSUD Sidoarjo Barat. The socialization was carried out by distributing leaflets containing information about the ease and how to make appointments using the RSUD Sidoarjo Barat online registration website, as well as a video on how to schedule online using the web. Out of the 32 participants in this activity, 13 respondents were able to schedule online using the website. In this socialization activity, obstacles were encountered such as patients who do not have a mobile phone, patients who prefer to register offline because they cannot use a mobile phone, and patients who lack support from their families. To maximize the utilization of the web-based online scheduling system, facilities and infrastructure are needed, such as system ease of use, compatibility of device specifications (smartphones), and support from staff to disseminate information to patients, such as through social media. In addition, support from the patient's family can help maximize the utilization of this system: